PARTISIPASI MASYARAKAT PADA PNPM MANDIRI PEDESAAN DALAM KONTEKS OTONOMI DAERAH (STUDI KASUS DI KAMPUNG PEPAS ASA KEC. BARONG TONGKOK KAB. KUTAI BARAT) - Nathanael . (Jurnal Paradigma (JP), 2017)
Participatory rural development program is a fundamental concept that has been releasing at long time ago and still be relevant in the future. Citizen participation in development was increased, and it leads to social welfare. To empower a member of society, government has declared the National Program of Society Empowering, Rural Autonomy which was implemented since 2007. The study results indicate that the degree of citizen participation in the PNPM activities at Pepas Asa Village is relatively low. Therefore, absolutely it is required to improve of society participation by optimizing the awareness activity and effectively socialization; and give prioritiy to capacity building of apparatus and citizen, not only to infrastructure development.